The role of adipose tissue immune cells in obesity and low-grade inflammation - Mraz, Milos; Haluzik, Martin (The Journal of endocrinology, 2014)
Adipose tissue (AT) lies at the crossroad of nutrition, metabolism, and immunity; AT inflammation was proposed as a central mechanism connecting obesity with its metabolic and vascular complications. Resident immune cells constitute the second largest AT cellular component after adipocytes and as such play important roles in the maintenance of AT homeostasis. Obesity-induced changes in their number and activity result in the activation of local and later systemic inflammatory response, marking the transition from simple adiposity to diseases such as type 2 diabetes mellitus, arterial hypertension, and ischemic heart disease. This review has focused on the various subsets of immune cells in AT and their role in the development of AT inflammation and obesity-induced insulin resistance.
Keywords: obezita; tuková tkáň; myeloidní buňky; immune cells; Humans; Lymphocytes; lymfocyty; Insulin Resistance; innate immunity; Inflammation; lidé; zvířata; zánět; low-grade inflammation; adipose tissue; inzulinová rezistence; insulin resistance; Myeloid Cells; Obesity; adaptive immunity; Animals; Adipose Tissue